Photocatalytic oxidation of clozapine using TiO2 immobilized in polystyrene: effect of operation parameters and artificial neural network modeling - Santana, Rayany Magali da Rocha; Moura, Thalita Cristhina de Lima; Nascimento, Graziele Elisandra do; Charamba, Lívia Vieira Carlini; Duarte, Marta Maria Menezes Bezerra; Napoleão, Daniella Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
In recent years, heterogeneous photocatalysis using semiconductors has proved to be efficient for the treatment of wastewater containing organic pollutants, such as drugs. Among some photocatalysts, titanium dioxide (TiO2) has been studied and applied for this purpose. Therefore, this work investigated the photocatalytic degradation of the antipsychotic clozapine under ultraviolet irradiation, using suspended and supported TiO2 in polystyrene material. Some experimental parameters were evaluated through a factorial design 23; a higher degradation rate of the compound was verified using 0.15 g of the immobilized catalyst, [H2O2] of 340 mg L-1 and pH 9, after 6 h of treatment. It was possible to obtain degradations above 93.48% and a two-stage model was proposed to describe the reaction kinetics. An artificial neural network was used to model the photocatalytic process and to determine the importance of the operational variables. It was also established that the use of this treatment resulted in 78.30% removal of chemical oxygen demand (COD) under optimized conditions. In addition, the stability of TiO2 support after five consecutive cycles was verified from reuse tests. However, by means of toxicological tests with Escherichia coli and Salmonella enteritidis, it was observed that the products generated by the reaction were more toxic than the original compound.